A 22-year-old woman with alcoholic pancreatitis and bilateral central scotomata - Dave, Tushar; Yap, Keith D.; Joe, Aaron W. (Digital Journal of Ophthalmology, 2024)
A 22-year-old woman presented emergently at Kelowna General Hospital, British Columbia, with a 3-day history of epigastric pain with radiation to her back. This was assessed to be alcoholic pancreatitis, and she was admitted to the hospital for supportive care. Approximately 2 hours into her admission, she reported new-onset, binocular, blurry vision but no pain, flashes, floaters, or scotomata. On the third day of admission, the patient reported new-onset, bilateral, patchy central vision loss. Given the evolution of her vision loss, the ophthalmology service was consulted.